Application of seismic isolation technique to partially filled conical elevated tanks. (15th November 2016) - Moslemi, Mehdi; Kianoush, M. Reza
Highlights: Passive control offers an improved solution for seismic design of elevated tanks. Sloshing height and convective pressure is amplified due to seismic isolation. Higher efficiency is observed in tanks having stiffer shaft structure. Isolations systems are more effective in slender tanks. There is an optimum value for the yield strength of isolators. Abstract: In the present study, the applicability of seismic isolation using lead-rubber and elastomeric bearings to liquid-filled conical elevated tanks is investigated. The supporting shaft structure is isolated either from the ground or from the vessel mounted on top by means of seismic isolators and the effect of such modification on dynamic response of conical elevated water tanks is investigated by performing finite element (FE) time-history analyses on various tank-pedestal models. The proposed FE method is capable of simulating the accurate three-dimensional behavior of the isolated elevated tanks involving the nonlinear hysteretic behavior of seismic isolators. Through this study, the effects of different parameters on the effectiveness of the seismic isolation system are investigated. The examined parameters include: lateral versus vertical isolation, locations of isolators, shaft stiffness, tank aspect ratio, and yield strength of isolators. The results of this study show the effectiveness of seismic isolation technique for these types of structures. It is concluded that the application of passive control devices to conical elevated water tanks could offer a substantial benefit for the earthquake-resistant design of such structures. The results of the study further show that the magnitude and distribution of seismically induced forces, moments and displacements could be controlled through appropriate selection of device properties, isolators' locations, and tank's structural and geometrical characteristics.